2023
DOI: 10.1088/2057-1976/acaf8a
|View full text |Cite
|
Sign up to set email alerts
|

Optimal digital filter selection for remote photoplethysmography (rPPG) signal conditioning

Abstract: Remote photoplethysmography (rPPG) using camera-based imaging has shown excellent potential recently in vital signs monitoring due to its contactless nature. However, the optimum filter selection for pre-processing rPPG data in signal conditioning is still not straightforward. The best algorithm selection improves the signal-to-noise ratio (SNR) and improves the accuracy of the recognition and classification of vital signs. We recorded more than 300 temporal rPPG recordings, where the noise is mainly not motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It is possible that Chebyshev type I and type II filters can find application in other tasks not related to the pulse wave analysis. For example, it was recently shown that the Chebyshev II filter of 2nd, 4th and 6th orders perform the best for denoising remote PPG signals in camera-based imaging technique 42 .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that Chebyshev type I and type II filters can find application in other tasks not related to the pulse wave analysis. For example, it was recently shown that the Chebyshev II filter of 2nd, 4th and 6th orders perform the best for denoising remote PPG signals in camera-based imaging technique 42 .…”
Section: Discussionmentioning
confidence: 99%
“… Publications by subject area [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , …”
Section: Figureunclassified
“…In the realm of remote photoplethysmography (rPPG), optimal digital filter selection becomes paramount for accurate vital signs recognition. The comparative analysis of 100 filters on over 300 rPPG signals reveals the Chebyshev II filter with a 4th order as the optimal choice for signal preprocessing [13].…”
Section: Introductionmentioning
confidence: 99%